2019
DOI: 10.3390/mca24040090
|View full text |Cite
|
Sign up to set email alerts
|

Lyapunov Exponents of Early Stage Dynamics of Parametric Mutations of a Rigid Pendulum with Harmonic Excitation

Abstract: This paper considers three dynamic systems composed of a mathematical pendulum suspended on a sliding body subjected to harmonic excitation. A comparative dynamic analysis of the studied parametric mutations of the rigid pendulum with inertial suspension point and damping was performed. The examined system with parametric mutations is solved numerically, where phase planes and Poincaré maps were used to observe the system response. Lyapunov exponents were computed in two ways to classify the dynamic behavior a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…It has also been confirmed that the proposed method can be much faster than other ones [12]. This algorithm has already been successfully applied in the fields of synchronization [13], time series analysis [14], systems with delays [15] and as a benchmark for comparison of results with other algorithms [16].…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…It has also been confirmed that the proposed method can be much faster than other ones [12]. This algorithm has already been successfully applied in the fields of synchronization [13], time series analysis [14], systems with delays [15] and as a benchmark for comparison of results with other algorithms [16].…”
Section: Introductionmentioning
confidence: 62%
“…The limit δ → 0 + is introduced due to the fact the perturbations to be transformed are infinitesimal. The matrix T x − , τ i presented in the expression (27) can be applied to calculate the quantities λ * * j according to the formulas (16) and (18), and thus to estimate the values of the LEs of the system (20) by means of the equation (17).…”
Section: Determining the Transition Matrix Of A Perturbationmentioning
confidence: 99%
“…Now, we will look at the variablelength pendulum with stiffness and damping as investigated by different authors. In [36] one finds an analysis without the damping force, while [37][38][39], and [40] include damping force in the analysis.…”
Section: If Resonance Appears At Frequencymentioning
confidence: 99%
“…This modification would give a faster and longer oscillation, which will, in turn, result in more rapid pumping of fluid since the variable-length pendulum can undergo a quicker and longer oscillation, as presented by the following authors: Ref. [12] derived the differential equations of dynamics for both the first and the second mutation from the sum of kinetic and potential energy for a rigid pendulum's two and three degrees of freedom. It was observed that a successive expansion in the forms of representation of the energy is introduced.…”
Section: Introductionmentioning
confidence: 99%